Integrated Traffic Safety Assessment Using Accident Equivalent Numbers And Road User Perceptions In Tana Toraja - Sombolinggi, Azril Tangke; Bua', Rilva Toding; Arrang, Abdias Tandy; Pakiding, Yulius (Jurnal Penelitian Sekolah Tinggi Transportasi Darat, 2026)
Traffic safety in mountainous regions is influenced by the interaction between infrastructure conditions, traffic exposure, and road user behavior. This study aims to analyze traffic accident characteristics and evaluate the influence of road user perceptions on accident risk on the Makale–Rantepao National Road in Tana Toraja, Indonesia. The study employed an integrated quantitative approach by combining objective historical data and subjective perception data within a single traffic safety framework. Secondary data consisted of traffic accident records from 2022–2025 and traffic exposure indicators, including vehicle ownership and population data from 2021–2024. Primary data were collected through a questionnaire survey involving 110 road users conducted in early 2026. Data analysis was performed using the Accident Equivalent Number (AEN) method, traffic exposure ratio analysis, descriptive statistics, and multiple linear regression. The results indicate that traffic accidents in Tana Toraja fluctuated during the study period, with the highest AEN recorded in 2022 at 815 and the lowest in 2025 at 351. Meanwhile, the vehicle-to-population ratio increased from 0.322 in 2021 to 0.373 in 2024, indicating increasing traffic pressure and exposure risk. Regression analysis demonstrates that road surface conditions, road safety facilities, and road user behavior significantly influence accident risk perception, with a coefficient of determination (R²) of 0.457. Among the independent variables, road surface condition showed the strongest influence on perceived accident risk. The findings suggest that integrating accident severity indicators, traffic exposure, and road user perceptions provides a more comprehensive understanding of traffic safety conditions in mountainous areas. This study contributes to the development of an integrated traffic safety assessment framework that can support sustainable road safety management and policy formulation in developing regions.